1996
DOI: 10.1172/jci118557
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6 enhances natural killer cell cytotoxicity via IL-15.

Abstract: The marked tropism of human herpesvirus-6 (HHV-6) for natural killer (NK) cells and T lymphocytes has led us to investigate the effect of HHV-6 on cellular cytotoxicity. We describe here how HHV-6 infection of peripheral blood mononuclear cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 26 publications
3
93
0
3
Order By: Relevance
“…In the present report, we describe augmentation of NK (4,7,8,24,55) and antitumor (20,67) host defenses. Target cell death mediated by NK cells is mediated by two predominant mechanisms: the Ca2 ϩ -dependent release of perforin and granzymes (77) and production of members of the TNF family of death-inducing ligands, such as FasL (42,57), TNF alpha (77), and TRAIL.…”
Section: Discussionmentioning
confidence: 53%
“…In the present report, we describe augmentation of NK (4,7,8,24,55) and antitumor (20,67) host defenses. Target cell death mediated by NK cells is mediated by two predominant mechanisms: the Ca2 ϩ -dependent release of perforin and granzymes (77) and production of members of the TNF family of death-inducing ligands, such as FasL (42,57), TNF alpha (77), and TRAIL.…”
Section: Discussionmentioning
confidence: 53%
“…It thus appears that IL-15 has potential roles in the development and maintenance of significant fractions of lymphocytes, including NK, NKT, TCR␥␦ i-IEL, and memory phenotype CD8 ϩ T cells. There have been several lines of evidence for IL-15 production in infection with various microbes, including M. tuberculosis (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). We have demonstrated that IL-15 is involved in protection against infections with Escherichia coli (35) …”
Section: P Rotection Against Infection With Mycobacterium Tuberculosimentioning
confidence: 99%
“…Given the ability of HHV-6 to modulate immune functions (33)(34)(35)(36)(37), eicosanoid synthesis modulation could play an important role in the pathogenesis of this virus, especially during the early steps of an infection. In the present work, we dissected the mechanisms by which HHV-6 up-regulates PGE 2 in monocytes/macrophages, and we identified the contribution of the different promoter elements in mediating COX-2 transcription.…”
mentioning
confidence: 99%